2016
DOI: 10.4236/psych.2016.72018
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Cognitive and Psychosocial Functioning in Children with Writing Disabilities

Abstract: The purpose of the study was to investigate the relationship between the Test of Detection and Investigation of Attention and Concentration, the Test of Executive Function (Simos et al., 2007a,b) and the Test of Psychosocial Adjustment and Self-Report Scale (Hatzichristou et al., 2007), in a sample of 44 Greek 5 th grade students with writing disabilities. The results in our study indicated that there were significant Pearson correlations ranged from 0.39 to 0.43 between cognitive, academic and social factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 56 publications
1
7
2
Order By: Relevance
“…Perhaps the differences between our findings and those of Alevriadou and Giaouri (2016) are related to the age of the participants in our sample and the measures used. Alevriadou and Giaouri (2016) had a slightly older sample of students (fifth graders) than our first– through fourth–grade sample.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Perhaps the differences between our findings and those of Alevriadou and Giaouri (2016) are related to the age of the participants in our sample and the measures used. Alevriadou and Giaouri (2016) had a slightly older sample of students (fifth graders) than our first– through fourth–grade sample.…”
Section: Discussioncontrasting
confidence: 94%
“…Taken together, these findings share both consistencies and inconsistencies with Alevriadou and Giaouri (2016), who showed that fifth grade students identified with a SLD–W exhibited attention deficits and low self–esteem. In the current study, AR–WD does present more frequently with behaviors rising to clinical significance, when examining the percentage of students’ scores falling above one standard deviation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Having listed some of our most important results, we hope that our research will contribute to further information and inform the educational community about the phenomenon of bullying and its causes. We hope that our research will contribute to informing teachers about school bullying and help them become effective in detecting and dealing with bullying incidents (Andersen et al, 2015). The knowledge of the relationship between learning difficulties and bullying will lead to the improvement in the handling of bullying issues that arise in the school context.…”
Section: Conclusion and Suggestionsmentioning
confidence: 92%
“…In the USA, in a study by Sabornie (2006), it was found that students attending general school integration classes had a limited number of friends, were socially marginalized, and exhibited passive behavior resulting in them on the one hand being victimized more often and on the other hand exhibiting an unexpected aggressive behavior in relation to typically developing students (A. Alevriadou, S. Giaouri. 2016;E.…”
Section: Literature Review: Research Data On the Relationship Between...mentioning
confidence: 99%